Size-dependent properties of single domain Fe2CoGa nanoparticles prepared by a facile template-less chemical route. Issue 33 (27th July 2022) - Srivastava, Manisha; Sahariah, Munima B.; Srinivasan, Ananthakrishnan
Abstract : Coercivity of Fe2 CoGa nanoparticles is superposed on typical single domain nanoparticle pattern. Magnetic hysteresis loop depicts superparamagnetism. HRTEM images show lattice fringes from (111) and (200) planes of inverse Heusler alloy structure. Abstract : Single phase X type Fe2 CoGa Heusler alloy nanoparticles with average crystallite sizes of 56 nm, 26 nm, and 21 nm have been synthesized using a refined template-less chemical route. Size-dependent structural and magnetic properties of the Fe2 CoGa alloy nanoparticles are compared with the bulk counterpart prepared by arc melting. Fe2 CoGa nanoparticles show soft ferromagnetic behavior with high magnetic moment and Curie temperature. Ab initio calculations have been carried out to interpret the experimental results. The estimated critical size and measured magnetic properties of the nanoparticles reveal that the synthesized nanoparticles are in a single domain superparamagnetic regime.